Ceftazidim-avibactam susceptibility of carbapenemase producing enterobacterales in an OXA-48 endemic area - Şevval Arduç Tok; Ayşe Barış; Leyla Genç; Hanife Tutan; Elif Aktaş (Journal of Global Antimicrobial Resistance)
Background: Carbapenem-resistant Enterobacterales (CRE) are included in the critical priority pathogens by WHO. OXA-48 is the predominating carbapenemase in Türkiye, in where carbapenem resistance rates are high, particularly in Klebsiella pneumoniae isolates. Ceftazidime-Avibactam (CAZ-AVI) has been used successfully in CRE infections in recent years, but resistance is reported to be on the rise. Aim: To evaluate the susceptibility to CAZ-AVI in CRE isolates and association of CAZ-AVI resistance and carbapenemase genes. Methods: CRE isolates from various clinical samples between January 2022 and June 2024 were included in the study. The isolates were identified by VITEK-MS(bioMerieux, France) system. Antibiotic susceptibilities were determined by VITEK COMPACT 2(BioMerieux, France) and CAZ-AVI susceptibility was evaluated by disk diffusion method(Oxoid, Thermo Fisher Scientific, Canada) according to EUCAST criteria. Carbapenemase genes were investigated in 324 representative isolates using Biospeedy Carbapenem-Resistance qPCR kit(Bioeksen, Türkiye). Results: The study included 429 CRE isolates. The distribution of CAZ-AVI susceptibility of CRE isolates according to sample type and clinics is shown in Table 1 and Table 2. CAZ-AVI susceptibility of isolates according to carbapenemase genes is presented in Table 3. In total, CAZ-AVI susceptibility of CRE isolates was 76%, while it was 99.5% in non-metallo-beta-lactamase (MBL) producers and 100% in only OXA-48-like producers. Conclusıons: Despite the increasing resistance in CRE isolates, CAZ-AVI is still a good option for treatment. CAZ-AVI was found to be highly effective particularly in isolates with non-MBL carbapenemase genes. Early detection of carbapenemase type is important in predicting CAZ-AVI susceptibility.